Knowledge, attitudes, and practices of chronic disease patients in Bojanala towards COVID-19 - Beya Mpinda; Cila Dominique Kabongo; Jean Louis Mata Yoko; John Tumbo (South African Family Practice)
Background: COVID-19 is an acute respiratory disease. Its morbidity and mortality in patients with comorbidities have been established. This study evaluated the knowledge, attitude and practices regarding COVID-19 of patients with comorbidities attending primary health care services.